2023
DOI: 10.1088/1742-6596/2623/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free Perovskites TlGeClxBr3-x (x=0,1,2,3) as Promising Materials for Solar Cell Application: a DFT Study

R K Pingak,
A Z Johannes,
N U J Hauwali
et al.

Abstract: This study investigates the structural parameters and the electronic properties of cubic TlGeClxBr3-x (x=0,1,2,3) lead-free perovskites to evaluate their potential as absorbers in perovskite solar cell devices. Density Functional Theory (DFT) embedded in the Quantum Espresso code was used to calculate these properties. The results revealed that the compounds have optimized lattice constants of 5.244 Å, 5.336 Å, 5.416 Å, and 5.501 Å, for TlGeCl3, TlGeCl2Br, TlGeClBr2, and TlGeBr3 perovskites, respectively. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…Similar trend was also observed for their vacancy ordered counterparts K 2 GeCl 6 and K 2 GeBr 6 [11] as well as Rb 2 GeCl 6 and Rb 2 GeBr 6 [13], where it was demonstrated that the anion substitution tunes the electronic band gap of the compounds. The progressive increase or decrease in the band gap energy as one of the cations of anions is substituted by an isoelectronic atom is characteristic feature observed across a wide range of perovskites [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. This implies that cation and anion substitution is an effective way to tune the electronic properties of materials, which is very important to realize specific application in optoelectronic devices.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Similar trend was also observed for their vacancy ordered counterparts K 2 GeCl 6 and K 2 GeBr 6 [11] as well as Rb 2 GeCl 6 and Rb 2 GeBr 6 [13], where it was demonstrated that the anion substitution tunes the electronic band gap of the compounds. The progressive increase or decrease in the band gap energy as one of the cations of anions is substituted by an isoelectronic atom is characteristic feature observed across a wide range of perovskites [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. This implies that cation and anion substitution is an effective way to tune the electronic properties of materials, which is very important to realize specific application in optoelectronic devices.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…The band gap value of CsInZrCl 6 is too large (3.6 eV) for solar cell applications. However, this value can be lowered by I doping since it has been shown that mixing Cl-based perovskites with Br or I led to a reduction in the band gap energy [47][48][49]. In addition, the band gap of the material can also be tuned by a number of approaches including chemical modification through anion exchange reactions [50], biaxial strain [51], structural templating [52], and hydrostatic pressure [53][54][55][56][57][58][59][60] CsInZrBr 6 , and CsInZrI 6 , with significantly higher contributions than the other states.…”
Section: Electronic and Bands Structures Propertiesmentioning
confidence: 99%